2017
DOI: 10.1002/mnfr.201600720
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of the total Western diet differentially affects the response to green tea in rodent models of chronic disease compared to the AIN93G diet

Abstract: Collectively, these observations indicate that the TWD influences the bioactivity of GTE in rodent models of obesity, metabolism, and carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Compared to the control group, the GTE group showed significant decreases in the cecal concentrations of acetate and butyrate, although their cecal pools returned to the control level. The same results were seen in previous studies in rats fed a diet supplemented with 6 g/kg EGCG (Unno et al., ) and in mice given a drinking water supplemented with 2 g/l GTE (Ward et al., ). It is known that acetate is produced by a variety of gut bacteria, but butyrate and propionate are produced by a distinct subset of bacteria.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared to the control group, the GTE group showed significant decreases in the cecal concentrations of acetate and butyrate, although their cecal pools returned to the control level. The same results were seen in previous studies in rats fed a diet supplemented with 6 g/kg EGCG (Unno et al., ) and in mice given a drinking water supplemented with 2 g/l GTE (Ward et al., ). It is known that acetate is produced by a variety of gut bacteria, but butyrate and propionate are produced by a distinct subset of bacteria.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study by our group demonstrated that the dietary addition of EGCG (6 g/kg), the most predominant polyphenol in green tea, lowered cecal levels of acetate and butyrate in rats (Unno, Sakuma, & Mitsuhashi, ). Recent investigation also revealed that the addition of green tea extract (GTE) (2 g/L) to drinking water increased wet mass of cecal digesta and decreased cecal SCFA concentrations in mice (Ward et al., ). Interestingly, regarding black tea extract (BTE), an in vitro model reflective of the distal region of the human large intestine recorded a different result suggesting that a continuous dose BTE may be capable of significantly increasing the levels of acetate during the fermentation (van Dorsten et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This study is the second from our group to show that the TWD functions to promote colon cancer in mice. Previously, we showed that A/J mice initiated with AOM and fed TWD for 16 weeks developed significantly more aberrant crypt foci and total crypt cells than mice fed the AIN93G diet [24]. Now, we report that consumption of TWD significantly enhanced tumorigenesis in C57BL/6J mice using both the AOM + DSS and Apc Min/+ + DSS models of CAC, whereas small intestinal tumorigenesis was not affected.…”
Section: Discussionmentioning
confidence: 77%
“…Results of the comparative transcriptomics analyses across DSS and IL-10 deficient mouse models, however, suggest that our TWD-enhanced DSS colitis model shares some similar transcriptional responses as observed in Il10 -/mice. Furthermore, we have investigated the effects of TWD in two mouse strains to date (C57BL/6J in this study and A/J males in [24]). However, given the influence of genetic background on susceptibility to inflammation and the progression of disease [69,70], a more extensive evaluation of strain-dependent responses to the TWD in context of gut inflammation would be valuable for future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation